Investigation of 0+ strength in 150Sm using the (p, t) reaction. (December 2020) - Ionescu, A.; Pascu, S.; Sima, O.; Faestermann, T.; Hertenberger, R.; Mihai, C.; Mihai, R.; Niƫă, C.; Turturică, A.; Wirth, H.-F.
Abstract: The aim of this investigation is to reveal the structure of 150 Sm by measuring for the first time a rather complete set of energy levels of this nucleus up to 4 MeV and determine the total angular momentum of the states. The study was carried out at the 14 MV Tandem Accelerator of the Munich universities by measuring complete angular distributions for states up to 4 MeV excited in the direct two-neutron transfer reaction 152 Sm(p, t) 150 Sm at an incident energy of 22 MeV. Emphasis was put on determining the 0 + excited states, which are some of the most important excitations in the rare-earth region. Up to now only three 0 + levels are known in 150 Sm, and investigating the distribution of energy and intensity of these excited states also at higher excitation energy might reveal the main contributions in the wave functions of this nucleus.